2013
DOI: 10.1007/s13402-013-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of the transcriptional coactivator YAP is associated with invasive lobular breast cancer

Abstract: BackgroundYes Associated Protein (YAP) has been implicated in the control of organ size by regulating cell proliferation and survival. YAP is a transcriptional coactivator that controls cellular responses through interaction with TEAD transcription factors in the nucleus, while its transcriptional functions are inhibited by phosphorylation-dependent translocation to the cytosol. YAP overexpression has been associated with different types of cancer, such as lung, skin, prostate, ovary and liver cancer. Recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 48 publications
10
59
0
Order By: Relevance
“…It may be through regulating cell proliferation; apoptosis, Epithelial Mesenchymal Transition (EMT), intercellular contact inhibition and self-renewal of stem cells that YAP participate in the occurrence and development of tumors [20][21][22][23][24], so it is considered as an oncogene. By immunohistochemical staining, researchers have found that YAP is upregulated in a wide variety of human cancers including liver cancer [25], breast cancer [26], lung cancer [27], gastric cancer, esophageal cancer [28] and colorectal cancer [29]. YAP was also found to be correlated with some skin and mucosa tumors, such as oral squamous cell carcinoma [30], malignant melanoma [31,32] and head and neck cancers [33].…”
Section: Discussionmentioning
confidence: 99%
“…It may be through regulating cell proliferation; apoptosis, Epithelial Mesenchymal Transition (EMT), intercellular contact inhibition and self-renewal of stem cells that YAP participate in the occurrence and development of tumors [20][21][22][23][24], so it is considered as an oncogene. By immunohistochemical staining, researchers have found that YAP is upregulated in a wide variety of human cancers including liver cancer [25], breast cancer [26], lung cancer [27], gastric cancer, esophageal cancer [28] and colorectal cancer [29]. YAP was also found to be correlated with some skin and mucosa tumors, such as oral squamous cell carcinoma [30], malignant melanoma [31,32] and head and neck cancers [33].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly focused gene, YAP1, was found to be involved in tumour development and progression in different malignancies, including CRC. Although increased level of the YAP1 protein (assessed by WB) was found in most studies [83,[88][89][90][91] suggesting its oncogenic role, the under-expression was also observed in breast [92] and colorectal cancer [79]. The study of Barry et al showed decreased expression of YAP1 in high grade tumours and stage IV [79].…”
Section: The Role Of Hippo Pathway In Colorectal Cancermentioning
confidence: 97%
“…Mouse KO: various cancer types developed [141] TSG: downregulation in CRC [142] TAZ Mutations in Barth syndrome [143] OG: overexpression in breast cancer [144], HCC [145] OG: overexpression in CRC [85] YAP1 OG: overexpression in NSCLC [88], prostate [90], breast [91], gallbladder cancer [146] and glioma [89] TSG: decreased expression in breast cancer [92] OG: overexpression in CRC [83], in CRC cases resistant to cetuximab [102] TSG: underexpression in CRC [79] AML -acute myeloid leukaemia; CCL -cancer cell line(s); HCC -hepatocellular carcinoma; KO -knock out; LOH -loss of heterozygosity; NSCLC -non-small cell lung cancer; OG -oncogene; TSG -tumour suppressor gene epinephrine or glucagon repress YAP1/TAZ activity [45,46]. YAP1 could also be regulated by matrix stiffness independently from LATS1/2 phosphorylation.…”
Section: Mob1 Mob1mentioning
confidence: 99%
“…For instance, the extent of nuclear TAZ or YAP levels corresponds with breast cancer tumor grade (2)(3)(4). In breast cancer cells, enhanced nuclear TAZ and YAP levels promote oncogenic transformation and endow cells with tumorigenic properties, including the ability to proliferate, subvert apoptotic cues, migrate, invade, and grow under anchorage-independent conditions (5-9).…”
mentioning
confidence: 99%